Age at marriage and marital instability: revisiting the Becker-Landes-Michael hypothesis - Evelyn Lilian Lehrer (Institute for the Study of Labor (IZA), 2006)
An early age at first marriage is known to be associated with a high risk of divorce. Yet it has been suggested that beyond a certain point, the relationship between age at marriage and marital instability may become positive, because as unmarried women begin to hear their biological clock tick, they may settle for matches far from the optimal. Analyses based on cycles 5 and 6 of the National Surveys of Family Growth show that the relationship between age at marriage and marital instability is strongly negative up to the late twenties, with a flattening of the curve thereafter.
Keywords: J12; J11; J10; 330; divorce; marital dissolution; marriage; Ehe; Zeit; Altersgruppe; Schätzung; USA